Periodontitis and atherosclerotic cardiovascular disease: A critical appraisal - Maria Clotilde Carra; Hélène Rangé; Giuseppina Caligiuri; Philippe Bouchard (2023)
Abstract In spite of intensive research efforts driving spectacular advances in terms of prevention and treatments, cardiovascular diseases (CVDs) remain a leading health burden, accounting for 32% of all deaths (World Health Organization. “Cardiovascular Diseases (CVDs).” WHO, February 1, 2017, https://www.who.int/news‐room/fact‐sheets/detail/cardiovascular‐diseases‐ (cvds)). Cardiovascular diseases are a group of disorders affecting the heart and blood vessels. They encompass a collection of different conditions, among which atherosclerotic cardiovascular disease (ASCVD) is the most prevalent. CVDs caused by atherosclerosis, that is, ASCVD, are particularly fatal: with heart attack and stroke being together the most prevalent cause of death in the world. To reduce the health burden represented by ASCVD, it is urgent to identify the nature of the “residual risk,” beyond the established risk factors (e.g., hypertension) and behavioral factors already maximally targeted by drugs and public health campaigns. Remarkably, periodontitis is increasingly recognized as an independent cardiovascular risk factor.